2011
DOI: 10.1152/ajpgi.00531.2010
|View full text |Cite
|
Sign up to set email alerts
|

Alanyl-glutamine promotes intestinal epithelial cell homeostasis in vitro and in a murine model of weanling undernutrition

Abstract: Alanyl-glutamine (Ala-Gln) has recently been shown to enhance catch-up growth and gut integrity in undernourished children from Northeast Brazil. We hypothesized that the intestinal epithelial effects of Ala-Gln in malnourished weanling mice and mouse small intestinal epithelial (MSIE) cells would include modulation of barrier function, proliferation, and apoptosis. Dams of 10-day-old suckling C57BL/6 pups were randomized to a standard diet or an isocaloric Northeast Brazil "regional basic diet," moderately de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 71 publications
(74 reference statements)
14
66
0
1
Order By: Relevance
“…In this study, using ex vivo mouse jejunal enteroids to complement an in vivo finding of crypt preservation in undernourished mice treated with oral Ala-Gln, a stable dipeptide previously shown to promote growth and gut integrity in undernourished children and mice (7,23), we demonstrate important effects of Gln and Ala-Gln on intestinal epithelial homeostasis. In enteroids, we found that Gln or Ala-Gln promoted mTOR signal activation, epithelial proliferation, and crypt expansion.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In this study, using ex vivo mouse jejunal enteroids to complement an in vivo finding of crypt preservation in undernourished mice treated with oral Ala-Gln, a stable dipeptide previously shown to promote growth and gut integrity in undernourished children and mice (7,23), we demonstrate important effects of Gln and Ala-Gln on intestinal epithelial homeostasis. In enteroids, we found that Gln or Ala-Gln promoted mTOR signal activation, epithelial proliferation, and crypt expansion.…”
Section: Discussionmentioning
confidence: 75%
“…We randomized wild-type C57/B6 dams with 10-day-old suckling pups to a multideficient regional basic diet (RBD) or an isocaloric, balanced control diet (CD), as previously described (22,23). Pups were weaned to their dams' diet (RBD vs. control) at 21 days of age and then subrandomized to ad libitum oral supplementation with a 111 mM solution of Ala-Gln (AminoStable, Ajinomoto) or plain drinking water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MTS and bromodeoxyuridine assays and increased epithelial cell apoptosis as measured by annexin and 7-aminoactinomycin D staining. All these changes were associated with decreased transmucosal resistance and increased permeability to FITC-dextran indicating intestinal barrier dysfunction [12].…”
Section: Undernutritionmentioning
confidence: 99%